Strategi Media Relations PT XL Axiata Tbk Dalam Menjalin Hubungan Baik Dengan Media Massa - Nadine Ilaf; Satya Candrasari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Media relations is a communication practice that is considered important by PT XL Axiata Tbk. The mass media itself is an intermediary tool that is used to distribute information or news about an institution. This is done to introduce and maintain a good image of the company that can influence public views. The purpose of this study was to determine the media relations strategy implemented by PT XL Axiata Tbk in establishing good relations with the mass media. This study uses a constructivism paradigm with a qualitative approach and descriptive methods. Data obtained from in-depth interviews. The sampling technique used is probability sampling with purposive sampling technique. The data analysis technique used is data reduction, data display and verification. The model used in this study is two way symmetric. From the results of this research analysis, the relationship carried out by PT XL Axiata Tbk with the media runs effectively that is with a relationship that has a reciprocity and mutual need. Suggestion from this research are expected that PT XL Axiata Tbk will continue maintain and develop their communication with the mass media.